2005
DOI: 10.1016/j.femsre.2005.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, vitality and activities of intestinal lactic acid bacteria and bifidobacteria assessed by molecular approaches

Abstract: While lactic acid bacteria and bifidobacteria have been scientifically important for over a century, many of these are marketed today as probiotics and have become a valuable and rapidly expanding sector of the food market that is leading functional foods in many countries. The human gastro-intestinal tract with its various compartments and complex microbiota is the primary target of most of these functional foods containing lactic acid bacteria and bifidobacteria (LAB&B). In addition, their use as vectors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 99 publications
4
35
0
2
Order By: Relevance
“…The great majority (up to about 80%) of these bacterial species have not been cultured. These numbers have mainly been assessed by molecular methods, counting both dead and live cells (34, 35). The advantage of our study is the possibility to explore the potential interplay between intestinal microbiota and human metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The great majority (up to about 80%) of these bacterial species have not been cultured. These numbers have mainly been assessed by molecular methods, counting both dead and live cells (34, 35). The advantage of our study is the possibility to explore the potential interplay between intestinal microbiota and human metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Using denaturing gradient gel electrophoresis (DGGE) of 16S rRNA gene amplicons, the same group later showed that the colonic mucosal microbiota and faecal microbiota were different, and the colonic mucosal microbiota was likely dependent on host factors [46]. Meanwhile fluorescent hybridization of probes for 16S rRNA genes was being applied to determine species identities, numbers, and proportions of intestinal bacteria [47, 48], exemplified by the studies of Dore, Blaut and colleagues [49, 50]. These analyses highlighted extensive inter-individual variation at phylotypes level (among northern Europeans) [49], and some correlations of microbiota with age, gender, and geographic origin but which varied between countries [50].…”
Section: The Normal Microbiota Of Humans and Animalsmentioning
confidence: 99%
“…In this report we have investigated the expression of class I heat shock genes in Lactobacillus plantarum , a lactic acid bacterium widely distributed in different environmental niches including the mammalian gastrointestinal tract [12]. Indeed, L. plantarum is considered an important component of the intestinal microbiota of healthy individuals and for its properties is considered a probiotic LAB [1,12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, L. plantarum is considered an important component of the intestinal microbiota of healthy individuals and for its properties is considered a probiotic LAB [1,12]. It is also widely distributed in most fermented products of animal and plant origin either as starter or as NSLAB [13], and more recently it has been used for nutraceutical productions [14].…”
Section: Introductionmentioning
confidence: 99%